O agente de inclusão escolar no apoio a alunos com deficiência intelectual: um estudo em escolas municipais de São Paulo - Duque, Luciana Fernandes (2016)
The main goal of this research was to critically analyze the role of the school inclusion agent on the support for intellectually disabled students, studying at municipal schools in Sao Paulo. The school inclusion agent is a professional linked/ bonded to a specialized institution that offers support to teachers and students from the standard schools, focused in the inclusion process. The methodological choice was the research qualitative ethnographic; all data were collected through questionnaires and interviews, wiling to know the role of the agent, the understanding of parents and teachers about the performance of this professional and also to raise all the questions related to the inclusion process. Another objective was to set situations that could contribute to the agent practice to the school inclusion of intellectually disabled students. This study was based on the idea that all the relations established between people, can be understood as relations of mediations and the mediators could be the family, the school, the teachers, the classmates and also the inclusion agent. It was possible to learn about the family, school and also the agent needs concerning the school inclusion; therefore it is possible to understand and motivate all the possible ways that in fact can contribute to an inclusive education with quality. It is clear that is in the school that we should focus all our efforts looking for changes in favor of people with disabilities; and the school inclusion agent is a professional that do this job to the standard schools. The aim for the quality of teaching is not a concern of the philosophies and professionals of the education area, but it is also for families, that so many times are not seen as a partner on this conquest.